Mine Wastes Characterization, Treatment and Environmental Impacts - Lottermoser, Bernd; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book provides a thorough, up-to-date overview of wastes accumulating at mine sites. It deals comprehensively with sulfidic mine wastes, mine water, tailings, cyanidation wastes of gold-silver ores, radioactive wastes of uranium ores, and wastes of phosphate and potash ores. The book emphasizes the characterization, prediction, monitoring, disposal and treatment as well as environmental impacts of problematic mine wastes. The strong pedagogical framework is supported by case studies from around the world, presentation of crucial aspects of mine wastes as scientific issues; end-of-chapter summaries as well as lists of resource materials and www sites for each waste type. The considerably updated third edition has novel and notable changes including: revision of text to reflect major developments and contemporary issues that are taking place in the field of mine waste science; new web pages at the end of each chapter; over 20 case studies and scientific issues; over 150 figures and tables; and an updated bibliography with over 1200 references. This newly balanced text will continue to equip the student and the professional with a thorough understanding of the principles and processes of mine wastes.
to Mine Wastes -- Sulfidic Mine Wastes -- Mine Water -- Tailings -- Cyanidation Wastes of Gold-Silver Ores -- Radioactive Wastes of Uranium Ores -- Wastes of Phosphate and Potash Ores.
Keywords: Geography; Hydraulic engineering; Mines and mineral resources; Waste disposal; Environmental pollution; Earth Sciences; Geotechnical Engineering & Applied Earth Sciences; Terrestrial Pollution; Mineral Resources; Waste Management/Waste Technology; Hydrogeology